IMPLEMENTASI MODEL PEMBELAJARAN BLENDED LEARNING PADA MATA KULIAH STUDI KELAYAKAN BISNIS MAHASISWA PRODI PENDIDIKAN EKONOMI UNIVERSITAS PGRI MAHADEWA INDONESIA - Putu Siti Firmani; Dewa Kresna Wirawan Kepakisan (LP3M Universitas PGRI Mahadewa Indonesia, 2022)
The shift in the implementation of learning activities in the world of education is felt today. When the Covid-19 pandemic emerged in early 2020, the implementation of direct learning activities was carried out online to anticipate the spread of this corona virus. The blended learning model is a learning model that combines face-to-face teaching methods with teaching methods using computer aids both offline and online to form an integrated learning approach. The research method used in this research is qualitative analysis. Qualitative research method is data that is described in detail in descriptive form which includes all data that does not use numbers (numbers), so that this qualitative data is in the form of words or sentences delivered orally or in writing regarding all patterns of human behavior that can be observed directly. Based on the results of interviews with the five informants above, they stated that the implementation of the blended learning model in the business feasibility study course at PGRI Mahadewa Indonesia University was good. The suggestions that researchers can give are that students at PGRI Mahadewa Indonesia University should be able to learn more about digital learning media used by higher education institutions in the teaching and learning process so that good two-way communication can be established from the application of the material provided.